MODERN FACILITIES AND PERFORMANCE OF IMO STATE MINISTRY OF WORKS, IMO STATE, NIGERIA - Ubah, Chukwudi Nelson (African Journal of Social and Behavioural Sciences, 2022)
This study focused on modern facilities and performance of Imo State Ministry of Works. The major goal is to determine the extent the use of modern equipment can add value to organisations and employee work effectiveness/efficiency. Four research objectives and four corresponding research questions and hypotheses were formulated. Survey research design was used to collect data through primary source (questionnaire). The population/ sample were the entire 167 staff in the works department of the Imo State Ministry of Works. Content and face validity were used in the validation of the questionnaire; and test-retest reliability method was adopted. The data collected were analysed using Mean Statistics and Pearson Product Moment Correlation Coefficient (PPMCC), at the 0.05 level of significance, through Statistical Package for Social Sciences (SPSS version 21.0). It was found that modern power supply facilities enhance employee service delivery; there is significant relationship between ICT facilities and efficiency of work. Also, modern security and safety facilities enhance effective safety management and there is significant impact of construction lifts and cranes on the productivity of work. The researcher recommends that organisations should always acquire and use modern facilities like modern power supply facilities, ICT facilities, modern security and safety facilities and construction lifts/cranes so as to achieve improved performance. More so, there is need for organisations to train and retrain their workers so that they can effectively use the modern facilities in performing their functions in order to achieve improved productivity. The study concludes that modern facilities add positive values to the effectiveness and productivity of modern organisations like Imo State Ministry of Works.